A new approach for the separation of spermatozoa from other cell types in forensically relevant samples. (December 2015) - Grosjean, F.; Castella, V.
Abstract: Due to imbalance in genetic material contribution, gynecological samples collected following a sexual assault are challenging to process in order to resolve the male contributor's DNA profile. We set up a new and fast procedure for the recovery and separation of cells from cotton swabs, or other supports. Using spermatozoa specific CD52 antibody coupled to magnetic beads along with magnetic columns, this procedure was first developed and optimized by flow cytometry. It allows the recovery of two enriched cell fractions: a sperm fraction, mostly enriched with the alleged offender's spermatozoa, and a non-sperm fraction, mostly enriched with cells from the victim. Processing fresh as well as six months old mock samples, made of buccal swabs loaded with sperm dilutions, resulted in full single NGM SElect DNA profiles of the sperm donors, respectively the epithelial cells donors, for the sperm and the non-sperm fractions. Untreated duplicate samples processed in parallel only provided the autosomal DNA profiles of the epithelial cells donors. This new procedure can be rapidly tested and adopted by forensic laboratories worldwide as it uses material already commercially available. Moreover it can be easily automated with existing platform, and could therefore provide a mean to rapidly reduce existing backlogs.